Post-stroke depresion and anxiety - D. Komsiyska; Y. Petkov (Trakia Journal of Sciences)
The aim of the study was to investigate the clinical features of depression and the relationship between depression and generalized anxiety disorder. Material and methods: 93 patients with stroke were examined, of whom 59 men (39-83 years) and 34 women (56-87 years), mean age 66.8 years. We used Patient Health Questionnaire (PHQ-9) and GAD-7. Results: Depressive disorder in the acute phase after stroke was found in approximately 2/3 (64.5%) of patients with stroke, with mild to moderate depressive disorders with low mood, increased mental and somatic anxiety, insomnia , somatic complaints, with extravagant hypochondriac thoughts. In our study we found significant positive correlation between depressive disorders and generalized anxiety disorders – and increase of severity of depressive disorders was followed by increase of severity of generalized anxiety disorders. We found high comorbidity between depression and generalized anxiety disorder.